FROM EXEMPLARITY TO TRADITION: THE DIALECTICS OF CONSTRUCTING RELIGIOUS MODERATION IN PESANTREN - Hendi Sugianto; Rofiqi Rofiqi; Abdul Rahim Karim; Samsul AR (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study examines how religious moderation education is constructed at Pesantren Darul Falah Ternate using Peter L. Berger’s social construction theory. A qualitative descriptive-analytical approach was employed, with data collected through in-depth interviews, participant observation, and document analysis. Data were analyzed using Berger’s three-stage dialectical framework: externalization, objectivation, and internalization. The findings reveal that religious moderation construction occurs through interconnected dialectical processes. Externalization manifests through the kyai’s charismatic exemplarity and comprehensive pesantren regulations. Objectivation involves inter-generational interactions that institutionalize values through the concept of barakah and habitualization processes. Internalization integrates universal Islamic teachings with Ternate local wisdom, particularly the “torang basudara” brotherhood tradition, creating contextual religious moderation that resonates with students’ cultural identities. The study demonstrates that religious moderation is not a fixed concept but a continuous social construction involving complex interactions among institutional structures, charismatic authority, peer relationships, and cultural resources. This research contributes empirical evidence showing how pesantren successfully translate abstract theological concepts into lived practices through holistic socialization processes, offering insights for developing contextually appropriate religious moderation education models.